(untitled) (The Research of Medical Science Review, 2025)
The objective of this investigation was to ascertain the prevalence and distribution of hydatid cysts and tuberculosis in slaughtered animals, as well as to identify the risk factors that are associated with these conditions in the districts of Dera Ismail Khan and Lakki Marwat, Khyber Pakhtunkhwa. An antemortem and postmortem examination of 139 cattle and buffaloes was conducted in 2023-24 as part of a cross-sectional observational survey from September 2023 to June Tuberculosis and hydatid cysts were identified through gross examination and further diagnosed using tissue samples through laboratory testing, which included the Ziehl-Neelsen staining method. Results showed that the animals examined did not contain any positive cases of tuberculosis or hydatid cysts, indicating no positive case detected at the slaughterhouse in sampled population. The investigation evaluated a variety of risk factors, such as the diagnostic capacity, human-animal interface, animal health history, biosecurity measures, and environmental conditions. It is important to note that 43.17% of the animals were exposed to high occupational levels, while 56.83% were exposed to low levels. The study underscored the necessity of rigorous biosecurity measures and continuous monitoring to protect public health, despite the absence of disease. These results emphasized the necessity of continuous vigilance to prevent potential outbreaks and underline the efficacy of the current control measures in the surveyed areas. The study provided valuable data for the development of strategies to maintain the health of both humans and animals and for future public health interventions.